Gender transformative food and nutrition training workshop report – Makueni County - Lutomia, Cosmas Kweyu; Ouya, Fredrick Ochieng'; Muema, Eunice; Njiru, Emerita; Nyamolo, Victor; Waswa, Boaz; Ketema, Dessalegn; Nchanji, Eileen (2025)
This report covers a gender-transformative nutrition training (GTNT) in Makueni County, convened under CGIAR’s Gender Equality and Social Inclusion Accelerator to support scaling of Gender-Transformative Socio-technical Innovation Bundling (GTSTIBs). Ninety-three participants from six sub-counties used participatory exercises and role plays to examine intra-household food allocation, learn ten food groups, and co-design actions. Sessions linked nutrition to bundles; intercrops, biofortified crops, kitchen gardens, gender and other social considerations. Participants agreed to integrate GTNT into routine county extension and health platforms and to track women and child dietary diversity.